THE RELEVANCE OF NATIONHOOD KNOWLEDGE IN MALAYSIAN STUDIES COURSES: A CONVEYANCE FOR NATIONAL UNITY AND AN INTEGRATION OF UNIVERSITY STUDENTS’ IDENTITY - Irma Wani Othman; Mohd Sohaimi Esa; Anna Lynn Abu Bakar; Saifulazry Mokhtar (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
This paper debates the relevance of knowledge of nationhood as a conveyance for national unity identity and integration of university students’ self-identity in addressing the issues and challenges of the Covid-19 post-pandemic era. In dissecting the significance of university student’s understanding of the Malaysian Studies course, the thrust of this discussion perspective works on the two-pronged objectives of (1) identifying the relevance of national unity identity issues of the younger generation, and (2) examining the challenges of applying National Principles as self-identity integration of university students. The synthesis of the discussion was also embroidered on the nurturing of the national language in society and the issue of compliance with the country’s constitution and laws. The qualitative approach utilises secondary data content analysis methods, namely the results of research in journals, reports, books and online news sources. The results of the study show that the course education of the nature of Malaysian Studies is a strong medium that can help understand the knowledge of nationhood and foster the retention of self-identity among students. The element of integration is also argued to place the relevance of university students to know the origin of a national identity and to avoid being influenced by external negative cultures. Naturally, each individual learns norms, values and habits through socialisation agents such as family, education, government and peers. Therefore, in the context of the relevance of learning and teaching elements that contain aspects of Malaysian Studies, understanding the knowledge of nationhood is a critical agenda for the future of the country where the formation of national identity must be inculcated in every student to strengthen national unity.